Length-weight relationship and environmental parameters of Macrobrachium malayanum (J. Roux, 1935) in Senggarang Water Flow, Tanjungpinang City, Riau Islands, Indonesia - Wahyu Muzammil; Tri Apriadi; Winny Retna Melani; Kurnia Dwi Handayani (Aceh Journal of Animal Science, 2020)
Macrobrachium malayanum (J. Roux, 1935) is a freshwater prawn occuring in Senggarang Water Flow, Tanjungpinang City, Riau Island, Indonesia. Least concern (LC) status of the IUCN red list threatened species and limited research about this species in Senggarang Water Flow cause this basic research is important to do. The objectives of the study were to examine the length-weight relationship of the M. malayanum in Senggarang Water Flow, Tanjungpinang City, Riau Island Province, Indonesia. A total of 84 samples were used in this study consist of 32 samples in February and 52 samples in April. Length-weight relationship of M. malayanum in February was W= 0.093TL1.425 (R2 = 0.59) and W=0.052TL2.195 (R2 = 0.75). Samples in February and April showed negative allometric growth. A temporal analysis of the negative allometric in b value showed in April (2.195) more larger than February (1.425). Environmental parameters such as temperature, current, dissolved oxygen, pH, salinity, nitrate, and phospate are still appropriate condition. M. malayanum found in substrate type slightly gravelly sand and gravelly sand.